Designing MOOCs to Facilitate Participant Self-monitoring for Self-directed Learning - Zhu, Meina; Bonk, Curtis J. (Online learning (Newburyport, Mass.), 2019)
This study investigates the design and delivery of MOOCs to facilitate student self-monitoring for self-directed learning (SDL) using mixed methods. The data sources of this study include an online survey with 198 complete respondents, semi-structured interviews with 22 MOOC instructors, and document analysis of 22 MOOCs. Study results indicated that MOOC instructors considered self-monitoring skills critical for SDL. To foster students’ self-monitoring, MOOC instructors reported that they facilitated students’ self-monitoring by helping students with internal feedback and providing external feedback. Students’ internal feedback includes cognitive and metacognitive processes. To facilitate cognitive processes, MOOC instructors provided quizzes, tutorials, learning strategies, learning aids, and progress bars. For metacognition, these instructors provided reflection questions and attempted to create learning communities. In addition, MOOC instructors, teaching assistants, and peers provided external feedback for students’ self-monitoring. Across these findings, technology played a central role in supporting student’s self-monitoring.